A new type of air-breathing photo-microfluidic fuel cell based on ZnO/Au using human blood as energy source. (29th November 2019) - Ovando-Medina, V.M.; Dector, A.; Antonio-Carmona, I.D.; Romero-Galarza, A.; Martínez-Gutiérrez, H.; Olivares-Ramírez, J.M.
Abstract: The purpose of this work was the evaluation of a microfluidic fuel cell (μFC), in which human blood glucose was photo/electrochemically oxidized. In this regard, ZnO/Au composites with different Au content (1, 2 and 3%) were synthesized, as well as physicochemical and electrochemically characterized. In order to know if these ZnO/Au composites would serve as photo-electrocatalysts in a μFC, their photo- and electrochemical activities were analyzed. In this sense, the optical band gap of composites was determined as 3.15 eV, showing the typical surface plasmon resonance between 530 and 550 nm, while the electrocatalytic activity of ZnO/Au composites was evaluated in terms of the 5 mM glucose, showing that the minimum negative potential shift of the glucose oxidation peak corresponds to the composite with 3% of Au content. A μFC was fabricated using ZnO/Au 3% as photo-anode under visible-light, Pt/C as air-breathing cathode, and human blood and air coming from environment as fuel and oxidant, respectively. It was observed that μFC presented a 1.5-fold more power density under visible-light than in the darkness. This work represents an advantage in the use of photo-electrocatalyst materials towards the development of a new type of air-breathing photo-microfluidic fuel cells employing physiological fluids opening the possibility to be used as a power source in non-implantable medical devices. Highlights: A new type of air-breathing photo-microfluidic fuel cell is presented. ZnO/Au composite is used as a photo-anode. An air-exposed Pt/C is employed as a cathode. The micro-device is operated using human blood as a glucose source. Visible light irradiated on the device increase the power density.